Mechanical Switching of Aromaticity and Homoaromaticity in Molecular Optical Force Sensors for Polymers. Issue 29 (27th April 2018) - Stauch, Tim
Abstract: The sensing of mechanical stress in polymers is indispensable for investigating the origin and propagation of cracks that lead to material failure and for designing mechanically responsive polymers. Here the unique approaches of using the force‐induced switching of aromaticity and homoaromaticity in molecular optical force sensors for the real‐time measurement of mechanical forces acting in stretched polymers are suggested. The mechanical switching of aromaticity in Dewar benzene is an irreversible event, whereas the degree of π‐orbital overlap in homoaromatic compounds like homotropylium can be adjusted progressively over a wide range of forces. Using computational methods, it is demonstrated that both approaches lead to significant changes in the visible part of the UV/Vis spectra of the force sensors upon application of weak forces (pN –nN ). Polymers that incorporate such molecular force sensors therefore change their color well before material failure occurs. Abstract : Binary versus continuous : Mechanical forces rupture Dewar benzene and flatten homotropylium, resulting in colored polymers.